Strategi KBRI Kuala Lumpur Dalam Perlindungan Kewarganegaraan: Studi WNI Tidak Berdokumen di Malaysia Tahun 2022–2023 - Aulia, Marzuqoh; Azizah, Nur (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The geographical proximity between Indonesia and Malaysia causes a high flow of mobilization in and out both legally and illegally. It was found that many Indonesian citizens did not have travel documents or passports and residence permits or visas. Based on Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia, this causes many Indonesian citizens to be threatened with losing their citizenship. Therefore, this research aims to find out the strategy of the Indonesian Embassy in Kuala Lumpur in protecting undocumented Indonesian citizens in Malaysia 2022–2023. The methods used in this research are observation, interview, and documentation. The results showed that the strategy in providing protection to undocumented Indonesian citizens by opening services at the Indonesian Embassy in Kuala Lumpur and issuing a Certificate of Indonesian Citizenship Status, conducting citizenship verification activities and making Travel Letters as Passports at the Immigrant Detention Depot, and holding in-depth discussions related to the problems of undocumented Indonesian citizens. This research will show that Indonesia realises its national interest in providing protection to undocumented Indonesian citizens in Malaysia through the Diplomatic Representative of the Republic of Indonesia in Kuala Lumpur by conducting bilateral cooperation with Malaysia.